La docencia universitaria desde los ojos de un comunicador - Bustamante Parodi, Sandra Libia (2020)
Nowadays, an integral communicator must develop a full view of the program. This perspective compromises not only communication tools that come together from the new information and the communication technologies, but also all those that correspond to the traditional field. Within this combination, University teaching is a fundamental pillar for soft skills development. This report reflects about the contribution of the communicator to teaching, the importance of emotions in education and finally, the teacher in a digital environment; through some cases that expose the construction of the learning design.